Automatic segmentation of digital images applied in cardiac medical images - Peres, F. A.; Oliveira, F. R.; Neves, L. A. [UNESP]; Godoy, M. F. (Institute of Electrical and Electronics Engineers (IEEE), 2010)
The digital image processing has been applied in several areas, especially where it is necessary use tools for feature extraction and to get patterns of the studied images. In an initial stage, the segmentation is used to separate the image in parts that represents a interest object, that may be used in a specific study. There are several methods that intends to perform such task, but is difficult to find a method that can easily adapt to different type of images, that often are very complex or specific. To resolve this problem, this project aims to presents a adaptable segmentation method, that can be applied to different type of images, providing an better segmentation. The proposed method is based in a model of automatic multilevel thresholding and considers techniques of group histogram quantization, analysis of the histogram slope percentage and calculation of maximum entropy to define the threshold. The technique was applied to segment the cell core and potential rejection of tissue in myocardial images of biopsies from cardiac transplant. The results are significant in comparison with those provided by one of the best known segmentation methods available in the literature. © 2010 IEEE.
Keywords: Cardiac imagens; Segmentation; Thresholding; Automatic segmentations; Digital image; Digital image processing; Initial stages; Maximum entropy; Medical images; Multilevel thresholding; Segmentation methods; Digital image storage; Feature extraction; Graphic methods; Health care; Heart; Medical imaging; Image segmentation